Preparation and polymerization of chalcone substituted aniline and investigation of impedance properties - Ahlatcioglu, Esma; Senkal, Bahire Filiz; Okutan, Mustafa; Gursel, Yesim (ELSEVIER SCI LTD, 2014)
New aniline derivative, containing substituted chalcone moiety was synthesized by starting from 3-amino acetophenone and 4-pyrridine carboxyaldehyde in the presence of NaOH. The obtained chalcone containing aniline was polymerized oxidatively in water in the presence of dopant such as methanesulfonic acid, formic acid, HBr and acetic acid using ammonium persulfate as oxidant at room temperature for 24 h. Chalcone containing polyaniline (Cs-PANI) was characterized by using FT-IR and physical methods. The impedance property of Cs-PANI has been successfully consolidated with existing electrical conductivity of conducting polymers. The obtained results suggest that Cs-PANI is a conductive polymer and the frequency exponent s is a correlated barrier hopping (CBH) and quantum mechanical tunneling (QMT) models, stating Jonscher's universal law. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Chalcone; Polyaniline; Oxidative polymerization; Conducting polymer; PHOTOCROSSLINKABLE POLYMERS; DIELECTRIC-PROPERTIES; FREQUENCY-DEPENDENCE; AC CONDUCTIVITY; PHOTOPOLYMER; FILMS; Engineering; Materials Science; Physics